(untitled) (Asian Education Studies, 2024)
This study investigates the resilience and efficacy of community-driven educational initiatives in the conflict-affected Karenni region of Myanmar, where traditional state-run schools have been destroyed or abandoned due to ongoing military conflict. Leveraging Collective Leadership Theory, the research explores how local communities sustain education through distributed leadership and collaboration. Using a mixed-methods approach, data from 249 teachers across 49 self-reliant schools were analyzed to understand the dynamics of community-driven education. The findings underscore the critical role of collective leadership and strong community involvement in maintaining educational continuity amidst severe disruptions. Despite significant obstacles, high levels of teacher satisfaction and effective community engagement highlight the success of these grassroots efforts. The study provides actionable recommendations for policymakers and practitioners to enhance educational resilience in similar conflict zones globally, emphasizing the importance of targeted support and recognition of local educators’ contributions.